2017
DOI: 10.5336/healthsci.2016-54418
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of "Food Craving Questionnaire" for Major Depression Patients into Turkish Culture: A Validity and Reliability Study

Abstract: Ö ÖZ ZE ET T A Am ma aç ç: : Bu çalışma; majör depresyon tanısı almış hastalarda kullanılmak üzere "Food Craving Questionnare (FCQ)" ölçeğinin Türkçe'ye uyarlaması için geçerlilik ve güvenirlilik çalışması yapmak amacıyla planlanıp yürütülmüştür. G Ge er re eç ç v ve e Y Yö ön nt te em ml le er r: : Çalışma 3 psikiyatri merkezinde, majör depresyon tanısı almış, yaşları 20-64 yıl arasında, toplam 203 (144 kadın, 59 erkek) hasta üzerinde yapılmıştır. Çalışmaya katılan hastalara 2 bölümden oluşan bir anket formu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
5
0
3
Order By: Relevance
“…Each item was scored from 1 to 6. Higher scores indicate that excessive food cravings have developed (Müftüoglu et al, 2017).…”
Section: Food Craving Questionnaire (Fcq)mentioning
confidence: 99%
See 1 more Smart Citation
“…Each item was scored from 1 to 6. Higher scores indicate that excessive food cravings have developed (Müftüoglu et al, 2017).…”
Section: Food Craving Questionnaire (Fcq)mentioning
confidence: 99%
“…VAS was used to digitize some values that cannot be measured numerically (Müftüoglu et al, 2017). In this study, individuals were asked to score some food types with VAS to determine which varieties they are most interested in.…”
Section: Visual Analog Scale (Vas)mentioning
confidence: 99%
“…Yapılan bir çalışmada, kadınların ABİS puanının erkeklerden daha yüksek olduğu saptanmıştır. 12 Yapılan çalışmalarda kadınlar ve erkeklerin farklı türdeki besinlere karşı istek duydukları; erkeklerin daha çok et, balık, yumurta vb. besinlere yönelik istekleri varken, kadınların hamur işi, dondurma, çikolata vb.…”
Section: İstati̇sti̇ksel Anali̇zunclassified
“…Bu hat düz olabileceği gibi, eşit aralıklar hâlinde bölünmüş de olabilir. Kişiler için elde edilen değerlerin ortalaması alınmaktadır 12. Bu çalışmada, bireylerin hangi besin türlerine daha fazla ilgi duyduklarını saptayabilmek amacıyla, bu besin çeşitlerini VAS ile puanlamaları istenmiştir.…”
unclassified
“…COVID-19 poses an unprecedented public health threat, which has led to an increase in uncertainty-related stress in many people especially people with obesity. 17 It has been observed that especially people with obesity try to cope with more stress during these periods. In quarantine periods, the difficulty in accessing food and the measures taken to reduce physical contact are also seen as the causes of stress in individuals.…”
Section: Discussionmentioning
confidence: 99%